(x³ + [tex]\frac{1}{8}[/tex])(2x² + 7x - 4) = 0
x³ + [tex]\frac{1}{8}[/tex] = 0 v 2x² + 7x - 4 = 0
x³ = - [tex]\frac{1}{8}[/tex] Δ = b² - 4ac = 7² - 4*2*(-4) = 49 + 32 = 81
x = ∛-[tex]\frac{1}{8}[/tex] √Δ = √81 = 9
x = -[tex]\frac{1}{2}[/tex] x₁ = [tex]\frac{-b-9}{2a}[/tex] = [tex]\frac{-7 - 9}{2*2}[/tex] = [tex]\frac{-16}{4}[/tex] = -4
x₂ = [tex]\frac{-b+9}{2a}[/tex] = [tex]\frac{-7+9}{2*2}[/tex] = [tex]\frac{2}{4}[/tex] = [tex]\frac{1}{2}[/tex]
x = {-4, -[tex]\frac{1}{2}[/tex], [tex]\frac{1}{2}[/tex]}